A New Best Approximation Result in (S) Convex Metric Spaces - M. Sabiri; J. Mouline; A. Bassou; T. Sabar (International Journal of Mathematics and Mathematical Sciences)
Consider a self-mapping T defined on the union of p subsets of a metric space, and T is said to be p cyclic if TAi⊆Ai+1 for i=1,…,p with Ap+1=A1. In this article, we introduce the notion of S convex structure, and we acquire a best proximity point for p cyclic contraction in S convex metric spaces.